2015
DOI: 10.1126/scisignal.aaa6179
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous roles for externalized cardiolipin in extracellular signaling: Promotion of phagocytosis and attenuation of innate immunity

Abstract: Among the distinct molecular signatures present in the mitochondrion is the tetra-acylated anionic phospholipid cardiolipin, a lipid also present in primordial, single-cell bacterial ancestors of mitochondria and multiple bacterial species today. Cardiolipin is normally localized to the inner mitochondrial membrane; however, when cardiolipin becomes externalized to the surface of dysregulated mitochondria, it promotes inflammasome activation and stimulates the elimination of damaged or nonfunctional mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 82 publications
(125 reference statements)
6
62
1
Order By: Relevance
“…We recently reported that concomitant exposure of cells to cardiolipin and lipopolysaccharide (LPS) in vitro inhibits the production of pro-inflammatory cytokines such as TNF-α by the cells22. However, these studies did not address the impact of cardiolipin in vivo on already established inflammation when cardiolipin levels increase in the extracellular milieu (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that concomitant exposure of cells to cardiolipin and lipopolysaccharide (LPS) in vitro inhibits the production of pro-inflammatory cytokines such as TNF-α by the cells22. However, these studies did not address the impact of cardiolipin in vivo on already established inflammation when cardiolipin levels increase in the extracellular milieu (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Finally, when released into the extracellular space, CLs on the surface of mitochondria or mitochondrial fragments, again mostly in their oxidized form, 35 can act as pro-phagocytotic 'eat me' signals via CD36 scavenger receptor and/or as suppressors of cytokine production potentially leading to immunoparalysis. 36 All these findings add to an emerging paradigm, namely that the myriad of different cellular lipid species, and in particular CL, have not just a supportive structural role, but are very actively involved in regulatory and signaling functions. 19,[37][38][39][40][41] …”
Section: Protein and Lipid Signaling In Mitophagy And Beyondmentioning
confidence: 99%
“…44 Beyond PtdSer, some other surface membrane moieties act as tolerogenic 'eat me' signals in a context-dependent manner (although the exact compositional balance of these with PtdSer is still debatable). These include externalized cardiolipin, 45 oxidized low-density lipoproteins, annexin-A1, thrombospondin, complement C1q and changes in membrane glycosylation status or charges (Figure 1). 6,15,46 Interestingly, in the context of chemotherapy-induced ICD, secretion of annexin-A1 by dying cancer cells followed by its binding to the formyl peptide receptor 1 on DCs, was found to facilitate recruitment of tumour-infiltrating DCs in close vicinity to the dying cancer cells and the formation of dead corpse/DC conjugates, resulting in immunogenic phagocytosis.…”
Section: Regulated Necrosismentioning
confidence: 99%